The algae names and collection of the Spanish Phycologist Pedro González Guerrero - Jose Luis Izquierdo; Francisco Pando (Anales del Jardín Botánico de Madrid, 2017)
In this paper we collect the 103 algae names published by the Spanish phycologist Pedro González Guerrero during his life-long study of algae at the Royal Botanic Garden of Madrid. Names are presented with specific information to facilitate the typification of these names in the future, since P. González only used small illustrations as type elements when describing new infrageneric taxa. We also review here the status of this collection, which has been restored and databased in the process. The collection currently comprises over 2150 specimens, a fraction of what it was a much larger one.